2022
DOI: 10.1037/tra0001094
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and intimate relationships in times of lockdown due to COVID-19.

Abstract: Objective: The virulence of COVID-19 has been particularly problematic in countries such as Spain. This led the government to decide that the population should be locked down at home to reduce the spread of the disease and avoid the collapse of the health system. Considering this, this study analyzed the changes in intimate relationships that occurred during lockdown in terms of dyadic adjustment, conflict, and quality of the relationship, as well as their relationship with anxiety symptoms. Method: Cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…Severe acute respiratory syndrome coronavirus (the causative virus of coronavirus disease 2019, COVID-19), first detected in Wuhan, China, in early December 2019, has been seen in many countries, threatens to be one of the most challenging tests faced by humanity in modern history ( Mahase, 2020 ; Pfefferbaum & North, 2020 ; Rodriguez-Dominguez et al, 2021 ; Wang, Horby, et al, 2020 ). So far, the COVID-19 has affected over 491 million reported cases (death rate, 1.28%), according to a recent report (April 4, 2022) from the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University( Johns Hopkins University, 2022 ).…”
mentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus (the causative virus of coronavirus disease 2019, COVID-19), first detected in Wuhan, China, in early December 2019, has been seen in many countries, threatens to be one of the most challenging tests faced by humanity in modern history ( Mahase, 2020 ; Pfefferbaum & North, 2020 ; Rodriguez-Dominguez et al, 2021 ; Wang, Horby, et al, 2020 ). So far, the COVID-19 has affected over 491 million reported cases (death rate, 1.28%), according to a recent report (April 4, 2022) from the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University( Johns Hopkins University, 2022 ).…”
mentioning
confidence: 99%
“…From that day on, the Spanish population faced situations of confinement in their homes for months: curfews, suspension of non‐essential services, mobility limitations, and other measures intended to reduce contagion levels (Ministerio de la Presidencia, 2020 ). These measures were focused on limiting physical contact and social and family relationships, having a significant psychological impact on the population by affecting emotional well‐being and mental health, with an increase in negative emotions, such as anxiety or depression, and sensitivity to social risks, as well as a decrease in positive emotions and life satisfaction (Rodríguez‐Domínguez et al, 2021 ). All this has contributed to increasing concern regarding health and family and reducing it when it came to leisure and friends (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the studied population actively sought information about the coronavirus, expressed a high level of concern and knowledge, especially those with greater psychological distress, and the most frequent preventive behaviour was hand washing and respiratory hygiene. As predictors of these circumstances, these authors identified the degree of concern about COVID‐19, the number of hours spent consulting information about the disease, or the need for psychological support, among others (Rodríguez‐Domínguez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations